1995
DOI: 10.1143/jjap.34.6458
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Behavior in Polyamides of m-Xylylenediamine and Dicarboxylic Acids

Abstract: We study the level spacing distribution p(s) in the spectrum of random networks. According to our numerical results, the shape of p(s) in the Erdős-Rényi (E-R) random graph is determined by the average degree k and p(s) undergoes a dramatic change when k is varied around the critical point of the percolation transition, k = 1. When k 1, the p(s) is described by the statistics of the Gaussian orthogonal ensemble (GOE), one of the major statistical ensembles in Random Matrix Theory, whereas at k = 1 it follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Recent research has shown that even‐odd polyamide 6,9 exhibit D‐E loops, although the ferroelectric activity is low . The ferroelectric hysteresis loop is also observed in quenched polyamide MXDn, and the nature of the ferroelectricity has been attributed to the amide groups in amorphous regions . Other polyamides such as polyamide 6I, 6T, 6I/6T copolymer, and BACn all exhibit ferroelectric behavior and clear D‐E hysteresis loops are obtained …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent research has shown that even‐odd polyamide 6,9 exhibit D‐E loops, although the ferroelectric activity is low . The ferroelectric hysteresis loop is also observed in quenched polyamide MXDn, and the nature of the ferroelectricity has been attributed to the amide groups in amorphous regions . Other polyamides such as polyamide 6I, 6T, 6I/6T copolymer, and BACn all exhibit ferroelectric behavior and clear D‐E hysteresis loops are obtained …”
Section: Introductionmentioning
confidence: 97%
“…19 The ferroelectric hysteresis loop is also observed in quenched polyamide MXDn, and the nature of the ferroelectricity has been attributed to the amide groups in amorphous regions. 20 Other polyamides such as polyamide 6I, 6T, 6I/6T copolymer, and BACn all exhibit ferroelectric behavior and clear D-E hysteresis loops are obtained. 21,22 However, there are few reports in the literature about piezoelectricity and ferroelectricity in odd-odd polyamides.…”
mentioning
confidence: 98%
“…This type of slow relaxation phenomenon has also been observed in the ferrodielectric polymer polyvinylidene fluoride. 15,16 While the hysteresis is not yet fully understood, by applying a voltage larger than the coercive voltage to the gate insulator in an effort to facilitate poling, we found that a large amount of charge ͑Q͒, which obeys Q = P r + CV, had accumulated at the interface.…”
mentioning
confidence: 89%
“…The odd nylons [53][54][55][56][57][58], which have all the carbonyl groups on the same side of the molecule, are indeed ferroelectric, with polarizations increasing with carbonyl content, ranging from 40 mC/m 2 to 130 mC/m 2 [56], which is comparable to the range for PVDF and its copolymers. The odd nylons are inexpensive and easy to process and make good piezoelectric [53][54][55] and pyroelectric [53,57,59] materials. Polarization switching, however, is hindered by hydrogen bonding between the =O and CH 2 on neighboring chains, making these materials difficult to polarize or switch.…”
Section: Other Ferroelectric Polymersmentioning
confidence: 99%